PERSEPSI SISWA TERHADAP MEDIA TELEVISI SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) (Studi Kasus di SMAN 8 Bogor) - Nouvaliano, Farell Fadillah (Komunika: Journal of Communication Science and Islamic Dakwah, 2021)
Da'wah is an activity that is timeless and applies throughout the ages. Da'wah also has many forms and ways, one of which is using television media. The Islamic da'wah program that airs on several Indonesian television stations can also be regarded as an Islamic religious education program on television. Because, audio-visual media can function as a medium for learning Islamic Religious Education. Learning media is an important factor in improving the quality of learning. This is due to the development of technology in the field of education that demands efficiency and effectiveness in learning. However, the results of learning using this media also depend on students' assessments and perceptions about learning Islam using television. This study uses a descriptive qualitative method by taking the resource person, namely one teacher who teaches Islamic Religious Education (PAI) and 7 students of class X and XI at SMAN 8 Bogor, the data obtained is processed using investigator triangulation analysis technique and source triangulation by comparing the results of interviews. to teachers and respondents, as well as test results. The results showed that the perception of students at SMAN 8 Bogor on PAI learning through television media, namely the Damai Indonesiaku program on TV One, was included in the medium category or 42.86%, the majority of students at SMAN 8 Bogor stated their agreement on the effectiveness of PAI learning by using television media. especially in the Damai Indonesiaku program on TV-One, although there were obstacles during the learning process with television media. Keywords: Television Media, Learning, Islamic Religious Education, Perception ABSTRAK Dakwah adalah sebuah kegiatan yang tak terbatas waktu dan berlaku sepanjang zaman. Dakwah juga memiliki banyak sekali bentuk dan cara, salah satunya menggunakan media televisi. Acara dakwah Islam yang tayang di beberapa stasiun televisi Indonesia juga dapat dikatakan sebagai acara pendidikan agama Islam di televisi. Karena, media audio visual dapat berfungsi sebagai media pembelajaran Pendidikan Agama Islam. Media pembelajaran merupakan salah faktor penting dalam peningkatan kualitas pembelajaran. Hal tersebut disebabkan adanya perkembangan teknologi dalam bidang pendidikan yang menuntut efisiensi dan efektivitas dalam pembelajaran. Walau demikian, hasil pembelajaran menggunakan media ini hasilnya juga bergantung pada penilaian dan persepsi siswa tentang pembelajaran Agama Islam menggunakan televisi. Penelitian ini menggunakan metode kualitatif deskriptif dengan mengambil narasumber yaitu satu orang guru pengampu pelajaran Pendidikan Agama Islam (PAI) dan 7 siswa kelas X dan XI di SMAN 8 Bogor, data yang diperoleh diolah dengan menggunakan teknik analisis triangulasi penyelidik dan triangulasi sumber dengan membandingkan hasil wawancara kepada guru dan responden, serta hasil test. Hasil penelitian menunjukkan bahwa persepsi siswa SMAN 8 Bogor pada pembelajaran PAI melalui media televisi yaitu acara Damai Indonesiaku di TV One termasuk dalam kategori sedang atau 42,86%, mayoritas siswa-siswi di SMAN 8 Bogor menyatakan persetujuannya terhadap efektifitas pembelajaran PAI dengan menggunakan media televisi khususnya dalam acara Damai Indonesiaku di TV-One, meskipun ditemukan kendala-kendala saat pembelajaran dengan media televisi ini berlangsung.